Experimental film and anthropology - Schneider, Arnd 1960-; Pasqualino, Caterina 1964- (Bloomsbury, 2014)
"Experimental Film and Anthropology urges a new dialogue between two seemingly separate fields. The book explores the practical and theoretical challenges arising from experimental film for anthropology, and vice versa, through a number of contact zones: trance, emotions and the senses, materiality and time, non-narrative content and montage. Experimental film and cinema are understood in this book as broad, inclusive categories covering many technical formats and historical traditions, to investigate the potential for new common practices. An international range of renowned anthropologists, film scholars and experimental film-makers engage in vibrant discussion and offer important new insights for all students and scholars involved in producing their own films. This will be indispensable reading for students and scholars in a range of disciplines including anthropology, visual anthropology, visual culture and film and media studies"--